Feedback using an ePortfolio for medicine long cases: quality not quantity. Issue 1 (December 2016) - Bleasel, Jane; Burgess, Annette; Weeks, Ruth; Haq, Inam
Abstract Background The evidence for the positive impact of an electronic Portfolio (ePortfolio) on feedback in medicine is mixed. An ePortfolio for medical long cases in a Graduate Medical Program was developed. The purpose of this study was to explore the perceptions of medical students and faculty of the impact of the ePortfolio on the feedback process. Methods In total, 130 Year 3 medical students, and six faculty participated in the study. This is a mixed methods study, using a combination of both quantitative and qualitative approaches. Quantitative methods were used to quantify the number of long cases performed. Qualitative methods were used to explore the relationship between quantity and quality of feedback, and provide a rich understanding of both students' and faculty's experience and perceptions of the ePortfolio. Results Students received a variable quantity of feedback at each of the three studied clinical schools, with an average of between 4 – 5.4 feedback episodes per student. Feedback that was constructive, specific and timely and delivered by a senior academic was important. Quantity was not an essential factor, with two episodes of detailed feedback reported to be adequate. The barriers to the use of the ePortfolio were technical aspects of the platform that interfered with student engagement. Conclusions Feedback using the ePortfolio for medical long cases is a valuable tool providing a senior clinician delivers detailed, constructive and personalized feedback in a timely fashion. The ePortfolio system needs to be user-friendly to engage students.